COMMUNITY SERVICE EDUCATION FOR HIGH RISK PREVENTION OF MOTHERS AND CHILDREN FROM AN EARLY AGE FOR ADOLESCENTS AT SMA NEGERI 17 MEDAN - Barirah; Rohmatun Nazilah; Yulia Amelia (Jurnal Masyarakat Indonesia (Jumas), 2024)
Prevention of high risks in mothers and children should not only begin during pregnancy, but must be prepared well in advance, namely from adolescence. In the Medan Tuntungan District area, especially in the SMA Negeri 17 Medan environment, it was found that the understanding of early detection of health risks still has a fairly wide psychological distance. Many adolescents as future parents are still in the shadow of traditional myths and local wisdom that sometimes contradicts the principles of medical safety. The program will be carried out on February 18, 2025 with interactive counseling methods and in-depth discussions to align the prevention of high maternal and child risk from an early age for adolescents. The results of the evaluation showed that there was an increase in participants' knowledge in recognizing the prevention of high maternal and child risk from an early age for adolescents, so that it is expected to be able to prevent high maternal and child risk from an early age for adolescents due to inappropriate actions. Prevention of high risks in mothers and children should not only begin during pregnancy, but must be prepared well in advance, namely from adolescence. In the Medan Tuntungan District area, especially in the SMA Negeri 17 Medan environment, it was found that the understanding of early detection of health risks still has a fairly wide psychological distance. Many adolescents as future parents are still in the shadow of traditional myths and local wisdom that sometimes contradicts the principles of medical safety. The program will be carried out on February 18, 2025 with interactive counseling methods and in-depth discussions to align the prevention of high maternal and child risk from an early age for adolescents. The results of the evaluation showed that there was an increase in participants' knowledge in recognizing the prevention of high maternal and child risk from an early age for adolescents, so that it is expected to be able to prevent high maternal and child risk from an early age for adolescents due to inappropriate actions.